Observational study of dabigatran etexilate 150 mg in patients with moderate renal impairment undergoing elective total hip or knee replacement. Issue 143 (July 2016) - Samama, Charles-Marc; Rosencher, Nadia; Kleine, Eva; Feuring, Martin; Brueckmann, Martina; Clemens, Andreas; Gullberg, Jenny; Frostick, Simon P.
Abstract: Introduction: The standard dabigatran etexilate dosage for prevention of venous thromboembolism (VTE) after elective total hip or knee replacement (THR/TKR) is 220 mg once daily (qd), with 150 mg qd for patients with moderate renal impairment. As clinical trial experience in patients with moderate renal impairment was limited at the time of approval, we conducted an observational study to evaluate the 150 mg qd dose. Materials and methods: This open-label, prospective, uncontrolled, observational study in patients with creatinine clearance (CrCl) 30–50 mL/min was conducted in seven European countries. Patients received 75 mg dabigatran etexilate 1–4 h after surgery and 150 mg qd on days 2–10 (TKR) or 2–35 (THR), per the European Summary of Product Characteristics. Coprimary outcomes were major bleeding events (MBEs) and a composite of symptomatic VTE and all-cause mortality. Results: 428 renally impaired patients with median CrCl 43.4 mL/min (range 30.0–49.9), and median age 80 years (range 32–96) received dabigatran etexilate: median treatment duration THR 31 days, TKR 28 days. Ten MBEs occurred in nine patients (2.1%; 95% confidence interval [CI]: 1.0–4.0; THR 1.8%; TKR 2.4%); none were fatal or involved a critical organ. Symptomatic VTE and all-cause mortality occurred in three patients (0.7%; 95% CI: 0.1–2.0; THR 0.9%; TKR 0.5%). Overall, 54 patients discontinued treatment prematurely, including 35 due to an adverse event (nine bleeding-related) and 16 switching to another anticoagulant. Conclusions: Dabigatran etexilate 150 mg qd had a good safety profile and was efficacious in fragile, elderly, renally impaired patients undergoing THR or TKR. These findings from the clinical practice setting add to the existing clinical trial data. Highlights: Observational study in moderately renally impaired hip/knee replacement patients Dabigatran etexilate dose: 150 mg once daily Incidence of symptomatic VTE/all-cause mortality 0.7%; major bleeding events 2.1% These were fragile, elderly, renally impaired patients. Dabigatran 150 mg once daily had a good safety profile and was efficacious.